Nitrogen-doped graphene supported palladium-nickel nanoparticles with enhanced catalytic performance for formic acid oxidation. (1st December 2016) - Jin, Yanxian; Zhao, Jie; Li, Fang; Jia, Wenping; Liang, Danxia; Chen, Hao; Li, Rongrong; Hu, Jiajie; Ni, Jiamin; Wu, Tingqian; Zhong, Danping
Abstract: Nitrogen-doped graphene (NG) supported palladium-nickel nanoparticles with uniform dispersion are synthesized as catalysts for the electro-oxidation of formic acid. The catalysts are characterized by X-ray powder diffraction (XRD), transmission electron microscope (TEM) and X-ray photoelectron spectroscopy (XPS). Our TEM results show that the Pd/Ni nanoparticles on NG are uniform with narrower size distribution than those on native graphene. XPS analysis reveals that Pd/NG and 1Pd1Ni/NG systems have more Pd 0 and less Pd 2+ content in comparison with the Pd/G and 1Pd1Ni/G counterparts respectively. This difference might be caused by the electron-donating effects of nitrogen species on the graphene surface. In addition, the electrochemical results show significantly enhanced catalytic activity and stability of 1Pd1Ni/NG as the catalyst for the formic acid oxidation reaction. The enhanced activity is not only attributed to the better uniform dispersion of nanoparticles and the enhanced electronic effect between metal particles and the support, but also ascribed to the synergistic effect of Ni incorporation to Pd.